Assessment of the adsorption kinetics, equilibrium and thermodynamics for the potential removal of Ni²⁺ from aqueous solution using waste eggshell - Aslan, Sukru; Polat, Ayben; Topcu, Ugur Savas (Journal of Environmental Engineering and Landscape Management, 2015)
In this study, Ni2+ sorption onto the waste eggshell was investigated under different operational conditions. Results indicated that the eggshell could be successfully used to remove Ni2+ ions from the water. Quick sorption process reached to equilibrium in about 2 hours with maximum sorption at pH 7.0. Based on the experimental data, Langmuir isotherm model with the qm value of 1.845 mg Ni2+/g eggshell was observed. The pseudo-second-order model provided the best correlation coefficient in comparison with other models. The calculated qe values derived from the pseudo-second-order for sorption of Ni2+ ions were very close to the experimental (qexp) values. Such thermodynamic parameters as ΔG°, ΔH°, and ΔS° were determined in order to predict the nature of adsorption. Results indicated that the adsorption of Ni2+ onto the eggshell was endothermically supported by the increasing adsorption of Ni2+ ions with temperature.